Poli Papers (2017)
his journal publishes high quality manuscripts that engage theoretical and empirical issues including education, social and technological sciences. They are tackled from a multidisciplinary perspective. The journal also features case studies focusing o
n practical implications, or papers related to learning and teaching in social and science disciplines, and finally, reviews on recent books. Articles published in the MUSE journal are of importance to academics, policy makers, practitioners and analy
sts in government and organizations, seeking to understand the diverse and complex characteristics of international environments. Though preferences are given to manuscripts that are international in scope, papers focused on domestic contexts and issu
es are also welcome, in order to facilitate the sharing of knowledge and potential generalizability of findings worldwide.